Respons Siswa terhadap E-LKPD Berbasis Discovery Learning Materi Transformasi Geometri - Ramadani, Desindra Rahmatia; Marhaeni, Nafida Hetty (CV. ITTC INDONESIA, 2024)
The research aims to determine the students' response to the use of Electronic Student Worksheet in mathematics learning. The instruments utilized in this study include a questionnaire on student responses and Electronic Student Worksheet based on liveworksheet. The population for this research consists of students from SMA Negeri 4 Yogyakarta in the XI MIPA 2 class. The sample comprises 31 students. The findings of this study indicate that the Electronic Student Worksheet based on liveworksheet receives an overall excellent response. The results show that students' responses to the Electronic Student Worksheet learning media in a small-scale trial, with an average score of 83.5, fall into the excellent category, while their responses in a large-scale trial, with an average score of 78.13, fall into the good category. Based on the analysis conducted, it can be concluded that learning outcomes significantly influence students' questionnaire responses in terms of the quality of content, technical quality, learning quality, and material suitability in Electronic Student Worksheet. Furthermore, it can be inferred from the student questionnaire responses that, overall, Electronic Student Worksheet based on liveworksheet is perceived to have excellent content quality, Electronic Student Worksheet appeal, learning quality, and suitability of language use in Electronic Student Worksheet.